Critical Inuit studies : an anthology of contemporary Arctic ethnography - Stern, Pamela R., 1958-; Stevenson, Lisa (University of Nebraska Press, 2006)
Critical Inuit Studies offers an overview of the current state of Inuit studies by bringing together the insights and fieldwork of more than a dozen scholars from six countries currently working with Native communities in the far north. The volume showcases the latest methodologies and interpretive perspectives, presents a multitude of instructive case studies with individuals and communities, and shares the personal and professional insights from the fieldwork and thought of distinguished researchers. The wide-ranging topics in this collection include the development of a circumpolar research policy; the complex identities of Inuit in the twenty-first century; the transformative relationship between anthropologist and collaborator; the participatory method of conducting research; the interpretation of body gesture and the reproduction of culture; the use of translation in oral history, memory and the construction of a collective Inuit identity; the intricate relationship between politics, indigenous citizenship and resource development; the importance of place names, housing policies and the transition from igloos to permanent houses; and social networks in the urban setting of Montreal.